Bullying Experiences of Adolescents with ADHD - Paulino, Jeffrey James (Archīum Ateneo, 2021)
Bullying is a prevalent problem among students. It is defined as repeated abuse of power which may come in the form of verbal or physical abuse or social exclusion. One population vulnerable to bullying are those with Attention-Deficit Hyperactivity Disorder (ADHD). Recent studies on bullying and ADHD have highlighted the prevalence and negative effects of this issue and suggested the need to investigate the personal experiences of bully victims. This study presents the meaning making of three adolescents with ADHD on their bullying experiences using Interpretative Phenomenological Analysis (IPA) as well as a clinical perspective. Findings show that bullying for these adolescents are conceptualized mainly by their struggles to cope and the negative emotions they ascribe to this phenomenon. Meanwhile, clinical perspective suggests that self-regulation, executive function issues, and lack of awareness on how ADHD symptoms manifest on their bullying response may shape their perception of this phenomenon. This study deepens the research on bullying particularly among those in the vulnerable population. The researcher emphasizes that the phenomenology of adolescents with ADHD and their bullying experiences are embedded mainly in their coping difficulties as it is aggravated by their symptoms. Recommendations for educational or clinical settings are offered and limitations of this study are discussed accordingly.